Composition of Haar Paraproducts - Wick, Brett (My University, 2014)
Paraproducts are important operators in harmonic analysis and there are well known characterizations of when an individual paraproduct is bounded. An interesting question is to characterize when the composition of two, potentially unbounded, paraproducts have a bounded composition. In this talk we will give necessary and sufficient conditions that characterize when the composition of certain compositions of Haar paraproducts are bounded
Keywords: Análisis matemático; Haar Paraproduct; Composition; Boundedness